Molecular Characterization of OXA-48-Like-Producing Enterobacteriaceae in the Czech Republic and Evidence for Horizontal Transfer of pOXA-48-Like Plasmids - Skalova, Anna; Chudejova, Katerina; Rotova, Veronika; Medvecky, Matej; Studentova, Vendula; Chudackova, Eva; Lavicka, Pavel; Bergerova, Tamara; Jakubu, Vladislav; Zemlickova, Helena; Papagiannitsis, Costas C; Hrabak, Jaroslav (Antimicrobial agents and chemotherapy, 2017)
The aim of this study was to characterize the first cases and outbreaks of OXA-48-like-producing Enterobacteriaceae recovered from hospital settings in the Czech Republic. From 2013 to 2015, 22 Klebsiella pneumoniae isolates, 3 Escherichia coli isolates, and 1 Enterobacter cloacae isolate producing OXA-48-like carbapenemases were isolated from 20 patients. Four of the patients were colonized or infected by two or three different OXA-48-like producers. The K. pneumoniae isolates were classified into nine sequence types (STs), with ST101 being predominant (n = 8). The E. coli isolates were of different STs, while the E. cloacae isolate belonged to ST109. Twenty-four isolates carried blaOXA-48, while two isolates carried blaOXA-181 or blaOXA-232 Almost all isolates (n = 22) carried blaOXA-48-positive plasmids of a similar size (∼60 kb), except the two isolates producing OXA-181 or OXA-232. In an ST45 K. pneumoniae isolate and an ST38 E. coli isolate, S1 nuclease profiling plus hybridization indicated a chromosomal location of blaOXA-48 Sequencing showed that the majority of blaOXA-48-carrying plasmids exhibited high degrees of identity with the pOXA-48-like plasmid pE71T. Additionally, two novel pE71T derivatives, pOXA-48_30715 and pOXA-48_30891, were observed. The blaOXA-181-carrying plasmid was identical to the IncX3 plasmid pOXA181_EC14828, while the blaOXA-232-carrying plasmid was a ColE2-type plasmid, being a novel derivative of pOXA-232. Finally, sequencing data showed that the ST45 K. pneumoniae and ST38 E. coli isolates harbored the IS1R-based composite transposon Tn6237 containing blaOXA-48 integrated into their chromosomes. These findings underlined that the horizontal transfer of pOXA-48-like plasmids has played a major role in the dissemination of blaOXA-48 in the Czech Republic. In combination with the difficulties with their detection, OXA-48 producers constitute an important public threat.
Keywords: bakteriální chromozomy; Enterobacteriaceae; Chromosomes, Bacterial; Plasmids; Bacterial Proteins; přenos genů horizontální; Česká republika; IncL; antibakteriální látky; beta-Lactamases; Microbial Sensitivity Tests; IncX3; Klebsiella pneumoniae; Escherichia coli; beta-laktamasy; ColE2-like; OXA-232; Gene Transfer, Horizontal; Czech Republic; Tn1999.2; Anti-Bacterial Agents; mikrobiální testy citlivosti; OXA-181; bakteriální proteiny; plazmidy; Tn1999.5